2013
DOI: 10.1038/bjc.2013.47
|View full text |Cite
|
Sign up to set email alerts
|

Frequent GNAS mutations in low-grade appendiceal mucinous neoplasms

Abstract: Background:The molecular basis for the development of appendiceal mucinous tumours, which can be a cause of pseudomyxoma peritonei, remains largely unknown.Methods:Thirty-five appendiceal mucinous neoplasms were analysed for GNAS and KRAS mutations. A functional analysis of mutant GNAS was performed using a colorectal cancer cell line.Results:A mutational analysis identified activating GNAS mutations in 16 of 32 low-grade appendiceal mucinous neoplasms (LAMNs) but in none of three mucinous adenocarcinomas (MAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
146
5
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(174 citation statements)
references
References 26 publications
18
146
5
1
Order By: Relevance
“…In that study, 89% of the mutations were in codon 12 and 11% in codon 13. In 2013, Nishikawa and colleagues identified GNAS mutations as common in LAMNs and suggested that mutant GNAS might play a direct role in mucin production (16 ).…”
Section: Discussionmentioning
confidence: 99%
“…In that study, 89% of the mutations were in codon 12 and 11% in codon 13. In 2013, Nishikawa and colleagues identified GNAS mutations as common in LAMNs and suggested that mutant GNAS might play a direct role in mucin production (16 ).…”
Section: Discussionmentioning
confidence: 99%
“…GNAS has been shown to elevate intracellular cAMP levels by stimulating adenylyl cyclase,17 which provokes cellular proliferation through the protein kinase A‐ERK signal pathway 18. Previous studies have detected these mutations in glandular neoplasms in the pancreas, colon, stomach, duodenum, and appendix16, 19, 20, 21, 22, 23, 24 Matsubara et al also identified GNAS gene mutations in 42% of LEGH 25. However, the relation among GNAS mutations, clinical courses and histological types of LEGH remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the widespread occurrence of G-protein-coupled receptors mutations the gene could in principle be involved in a large number of different tumor types. And indeed, it was shown that GNAS1 mutation could be found in different neoplasia throughout the whole body ranging from pituitary gland tumors [12] over www.fhc.viamedica.pl pancreatic intraductal papillary mucinous neoplasm (IPMN) [13,14], low-grade appendiceal mucinous neoplasia [15], villous adenomas of the colorectum [16] to colorectal carcinoma [17]. However, the mutation status of GNAS1 in gastrointestinal cancer has not yet been well investigated.…”
Section: Introductionmentioning
confidence: 99%